How cross-functional management influences new product development: a socio-technical perspective. Issue 9 (20th October 2016) - He, Yuanqiong; Sun, Hongyi; Chen, Yun
ABSTRACT: This paper develops an integrated theoretical framework of cross-functional management from a socio-technical perspective, focusing on technical support, job rotation and process standardisation. It then explores the effects of these three practices on new product development (NPD) via a global survey of 725 manufacturing companies in 20 countries. The results show that technical support and job rotation are positively related to the speed of NPD, while process standardisation and job rotation are positively associated with the quality of new products. These results contribute to the field of NPD by integrating the technical and social aspects of cross-functional management.